Śledzie and Soda Bread: Are Intercultural Events Truly Intercultural? - Marshall, Tom (Irish Journal of Arts Management and Cultural Policy, 2021)
Intercultural events, particularly one-off ‘fun-days’ present displays of cultural stereotypes where dialogue is superficial undermining inter-community interaction. Local funding policies may also contribute to the lack of diverse and long-term (trans)local dialogue. "This article argues that particular intercultural events hinder, rather than foster the cohesion of heterogeneous local communities. Intercultural events range from intimate one-off or long-term interactions to large ‘fun-days’; the latter entice local communities to congregate in contrived spaces. Intercultural ‘fundays’ encourage translocal communities to display their material culture as a gaze for local-born actors. I argue that intercultural fun-day displays of material culture are unrepresentative of a nation or translocal individuals. Does śledzie (herrings) represent Poland or soda bread, Northern Ireland (NI) or? I consider that one-off intercultural events maintain and perpetuate divisions which they attempt to heal, rather than encouraging intergroup understanding of (trans)local groups’ lifeworlds. Additionally, publicly funded intercultural events are required to demonstrate that grants are suitably spent and well-managed in line with predetermined variables. Therefore, cultural funding policies may inadvertently favour organisations with bureaucratic expertise, over small community groups with rich (trans)local knowledge. The perspective of body hexis, based on participant observation at intercultural fun-days in NI, make it possible to problematise them as insufficient to engender cohesion between (trans)local communities. Conversely, I argue that genuine intercultural appreciation is possible and sustainable when (trans)local communities dialogue together"